Forests and Plastic Wastes: A Natural Parasitic Relationship with the Concept of Sustainable Forestry - Datta, Neelabh (Journal of Sustainable Materials Processing and Management, 2022)
Sustainable Forest Management refers to the management and utilization of forests and their biodiversity, productivity, reproducibility potential and prospective in the relevant environment, both now and in the future in a manner that does not harm economic and social outputs at different levels, which creates socially equitable, environmentally sound and economically viable outcomes. Proper and sustainable plastic waste management is now seen as a necessity for sustainable forest use, leading to the setting of ambitious targets for recyclability as well as incorporating recycled plastics into products. For the scientific and forest management community, the challenges hindering efforts to mitigate plastic pollution are identified to inform the recommendations presented and emphasize the urgency of finding sustainable solutions to plastic pollution that do not only address the existing issues faced by forests and environments but also future threats presented by plastic pollution. Another way that plastic impact wildlife and forests is by releasing additives such as phthalates and Bisphenol A (BPA) into food chains which disrupts hormone system of vertebrates and invertebrates because they release substances that generate hormone imbalances. Plastic wastes manage to enter into and harm numerous biological functions of animals. In this article concept of sustainable forest practices and addressing the impact of plastic waste on the forests and environment before and during the COVID-19 epidemic are highlighted along with current sources of plastic wastes which manage to enter the environment. With sustainable forestry practices, plastic waste can be reduced, which has a positive impact on the ecosystem.